The Lexical -Semantic Field of the Concept "Mourning" In the Uzbek Language Structure (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article says about the consistent removal of the differences, the designating signs of the concepts ‘boredom’, ‘sadness’, “sorrow’, ‘grief’, and graphically presents them as a mental paradigm in the form of conceptual square. Identified on the basis of classical texts, denotative marks allow to build semantic constants, to construct semantic constants, and to create a metatext of such emotion’s complete definition, in accordance with its understanding by Uzbek native speaker. The description of the concepts presents them in their systematic relationship to each other in the sequence of emotion’s development: boredom plays a role of the origin of a“primary-sense” conceptum, which is fi guratively represented by ‘melancholy’, as a notion it is represented by ‘sadness’, and symbolically it is represented by ‘sorrow’; the last one unites sadness and melancholy. The concept under scrutiny is the basic one, since it is expressed in the language by common lexical signs, which are explicitly representing the meaning of the concept.The article says about the consistent removal of the differences, the designating signs of the concepts ‘boredom’, ‘sadness’, “sorrow’, ‘grief’, and graphically presents them as a mental paradigm in the form of conceptual square. Identified on the basis of classical texts, denotative marks allow to build semantic constants, to construct semantic constants, and to create a metatext of such emotion’s complete definition, in accordance with its understanding by Uzbek native speaker. The description of the concepts presents them in their systematic relationship to each other in the sequence of emotion’s development: boredom plays a role of the origin of a“primary-sense” conceptum, which is fi guratively represented by ‘melancholy’, as a notion it is represented by ‘sadness’, and symbolically it is represented by ‘sorrow’; the last one unites sadness and melancholy. The concept under scrutiny is the basic one, since it is expressed in the language by common lexical signs, which are explicitly representing the meaning of the concept.